2140. Healthcare-Associated Infection Outbreak Investigation of an Elevation of Surgical Site Infections at a Critical Access Hospital. (26th November 2018) - Pedati, Caitlin; Sullivan, Madison; Drake, Margaret; Leisy, Melody; Safranek, Tom; Tierney, Maureen
Abstract: Background: Reported incidence of surgical site infections (SSIs) in the United States commonly ranges from approximately 0.5–20%. An infection preventionist at a critical access hospital (CAH) notified the Nebraska Department of Health Human Services (NDHHS) Healthcare-Associated Infection (HAI) program of a surgeon with a 6-month SSI rate of 29% ( N = 7) and requested assistance. Methods: NDHHS HAI program and local health department personnel conducted an investigation. Overall SSI rates were calculated, and seven reported SSI charts were abstracted using the Centers for Disease Control and Prevention's HAI Outbreak Investigation Form. An additional nine-patient charts with similar characteristics were abstracted and used as the control group. These cases had the same procedures performed at the same facility, by the same surgeon, and during the same period of time but did not develop infections. Results: In 2016, of the 452 procedures at this CAH, 17 developed SSIs (rate = 3.8%). SSIs occurred following the most invasive procedures being performed on the sickest patients at this CAH. Of the 17 SSIs, 15 (88.2%) were orthopedic and performed by three surgeons. Surgeon A performed 24 procedures with seven SSIs (rate = 29.2%). Surgeon B performed 171 procedures with five SSIs (rate = 2.9%) and Surgeon C performed 13 procedures with three SSIs (rate = 23.1%). The seven SSIs associated with Surgeon A used different operating room (OR) personnel, rooms, antibiotics, and durations. There were 0 deaths. The seven SSIs and nine controls were evaluated using a stepwise regression model. Using the variables for bone graft, hardware, OR location, and number of people in the OR, the only significant variable was the number of people in the OR. There was an average of 10 people in the OR among cases and seven among controls. Logistic regression yielded an odds ratio of 1.8 (95% CI: 0.99–3.26). Conclusion: SSIs occurred primarily after orthopedic procedures, and two of three surgeons were found to have elevated rates. Analysis showed the number of people in the OR was potentially associated with SSIs. After following NDHHS recommendations to limit door openings and OR traffic, there were no additional cases. Additionally, we outlined our methodology in a publically-available response guideline posted to the NDHHS web page. Disclosures: All authors: No reported disclosures.